2012
DOI: 10.1007/s12094-012-0756-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and predictive value of CA-125 in the primary treatment of epithelial ovarian cancer: potentials and pitfalls

Abstract: The serum cancer antigen 125 (CA-125) remains a reliable biomarker in the therapeutic management of epithelial ovarian cancer (EOC). Monitoring the efficacy of cytotoxic chemotherapy (CT) and the early detection of relapse during the follow up of patients in remission represent the two most common clinical situations where the CA-125 has been successfully applied. There are however other scenarios along the course of the disease where the CA-125 can potentially aid in the decision-making process. Preoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 46 publications
(42 reference statements)
0
14
0
1
Order By: Relevance
“…Since its first introduction as a glycoprotein epithelial surface tumor marker in epithelial ovarian cancer with particular use for follow-up monitoring of disease activity, 16 serum CA-125 has widely been used as an important biomarker in the management of women with ovarian cancer. 17 Elevated CA-125 levels were also shown to be a strong predictor of poor prognosis in patients with endometrial cancer. 18 These findings support our result that CA-125 is a prognostic factor even in synchronous endometrial and ovarian cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Since its first introduction as a glycoprotein epithelial surface tumor marker in epithelial ovarian cancer with particular use for follow-up monitoring of disease activity, 16 serum CA-125 has widely been used as an important biomarker in the management of women with ovarian cancer. 17 Elevated CA-125 levels were also shown to be a strong predictor of poor prognosis in patients with endometrial cancer. 18 These findings support our result that CA-125 is a prognostic factor even in synchronous endometrial and ovarian cancers.…”
Section: Discussionmentioning
confidence: 99%
“…CA 125 is undoubtedly the most carefully studied and extensively used biomarker despite being characterized as having low sensitivity and specificity [85]. Many gynecologic and nongynecologic pathological conditions showed increased serum levels for this marker such as endometriosis and adenomyosis, pelvic, peritoneal, pleural, and musculoskeletal inflammatory diseases, hepatitis, and pancreatitis [81, 86].…”
Section: Mv-associated Mirnas As Possible Biomarkers For Human Ovamentioning
confidence: 99%
“…Many of the related studies focus on specific values of CA-125. For example, studies on absolute CA-125 values have shown that the CA-125 levels after surgery, after 2, 3, or 6 cycles of chemotherapy are important prediction factors for OS [16-20], but the preoperative CA-125 may not correlate with OS [21]. The results presented here also suggested that those patients survived <3 years had an overall higher CA-125 curve compared to those who survived 3 years or more, even in the first month of treatment, which typically represents the CA-125 changes after the first couple of chemotherapy cycles.…”
Section: Discussionmentioning
confidence: 99%